Gelatine sponge application in myoma bed to achieve hemostasis during myomectomy – A pilot study - Pal, Manidip; Chatterjee, Suvanjan; Bandyopadhyay, Soma (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: To study the efficacy of gelatine absorbable sponge to achieve hemostasis of myoma bed during myomectomy. Materials and Methods: Patient < 40 years with diagnosis of fibroid planned for myomectomy were included. Local infiltration around myoma was done with vasopressin diluted with normal saline (10 units of vasopressin mixed with 100 ml of normal saline). Myomas are easily removed. Gelatin absorbable sponge was applied over the myoma bed and the bed was closed. Proper hemostasis was maintained. Hb deficit was measured postoperatively. Results: Fifteen cases were studied. Vasopressin (diluted) administration ranged from 30-200 ml. Intra-operative blood loss of about 50 ml was noticed in 6 cases, 80 ml – 3 cases, 100 ml – 3 cases, 200 ml – 2 cases, 400 – 1 case. Duration of operation ranged from 60 – 150 minutes. Pre and post-operative Hb% estimation revealed that there was no change in Hb% in 3 cases. Conclusion: Gelatin absorbable sponge application over the myoma bed while closing the area is a good technique to achieve hemostasis during myomectomy. Asian Journal of Medical Sciences Vol.7(4) 2016 19-23